Lunatics and Prophets. The Influence of the Philosophy of the 19th Century on the 20th Century Avant-Gardes - Rybkowska, Alicja (Hybris, 2017)
The paper is devoted to the 19th century conceptions of the relation between the individual and the society and their influence on art. It will be discussed on the example of Ernest Renan and Hippolyte Taine. Close analysis and explication of these two philosophies will show that the influence is, in fact, always two-way: an individual takes inspiration from the prevailing world-view and at the same time can co-form it. As a result of a comparative study of art and philosophy, further perspectives for the research on the influence of the “intellectual climate” on the art of the early 20th century will be drawn.